The Influence of Corporate Social Responsibility and Corporate Image against a Loyalty customers (Case study on fast-food restaurant McDonald's Indonesia Semarang) - Lutfi Inayah Astuti; Rodhiyah Rodhiyah (Universitas Diponegoro, 2017)
the activities of Corporate Social Responsibility has become a liability for the company. In addition to these activities can enhance citra peruahaan and customer loyalty. The last time the development in some of the fast-food restaurant in Indonesia is growing increasingly rapidly, such as in Semarang city McDonalds already held a variety of Corporate Social Responsibility activities. However, there are still customers do not know the activities of Corporate Social Responsibility and corporate image that exists so that the causes of low customer loyalty. This research type is explanatory research with engineering data collection questionnaire with accidental sampling method. Because the number of populations unknown then according to Emory and Cooper (1997) sampled in this study amounts to 100 respondents who is a customer of McDonalds in the city of Semarang. With a test with test validity, reliability, cross-tabulations, coefficient of correlation, simple regression analysis, the determination coefficient, test of significance (t-test), and test results of f. this research concluded that Corporate Social Responsibility a positive and significant effect against the corporate image, Corporate Social Responsibility and positive effect significantly to customer loyalty. Influential positive corporate image against customer loyalty, as well as Corporate Social Responsibility and corporate image effect positive customer loyalty